2014
DOI: 10.1038/nature13176
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic alterations in oesophageal squamous cell cancer

Abstract: Oesophageal cancer is one of the most aggressive cancers and is the sixth leading cause of cancer death worldwide. Approximately 70% of global oesophageal cancer cases occur in China, with oesophageal squamous cell carcinoma (ESCC) being the histopathological form in the vast majority of cases (>90%). Currently, there are limited clinical approaches for the early diagnosis and treatment of ESCC, resulting in a 10% five-year survival rate for patients. However, the full repertoire of genomic events leading to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

64
950
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 934 publications
(1,049 citation statements)
references
References 36 publications
64
950
7
1
Order By: Relevance
“…Finally, our results indicated that female sex was independently associated with better OS and PFS, similar to a previous study [34].Previous research [30] also indicated that the risk of esophageal squamous cell carcinoma correlated with alcohol consumption and that drinking was a prognostic factor for OS in univariate (p = 0.010) and multivariate analyses (p = 0.037). This is also in agreement with our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, our results indicated that female sex was independently associated with better OS and PFS, similar to a previous study [34].Previous research [30] also indicated that the risk of esophageal squamous cell carcinoma correlated with alcohol consumption and that drinking was a prognostic factor for OS in univariate (p = 0.010) and multivariate analyses (p = 0.037). This is also in agreement with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were reported in a study of patients with nasopharyngeal carcinoma who were treated by IMRT [29]. These results suggest a common underlying pathogenesis for esophageal squamous cell carcinoma (ESCC) and head and neck squamous cell carcinoma (HNSCC) [30]. Our patients with stage I and II cancer had significantly better OS and PFS than those with stage III and IV cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Loss-of-function mutations in Notch1 are found in diverse epithelial cancers. Notch mutations may predict Wnt dependency and sensitivity to upstream inhibitors, but confirmatory studies are needed (60).…”
Section: Loss-of-function Mutations In Notch Ligandsmentioning
confidence: 99%
“…For example in oesophageal SCC, the frequency of ctnnb1 mutations is only 1.1%, but yet 86.4% of oesophageal SCC tumours contain mutated WNT pathway genes (Song, et al 2014), suggesting the mechanisms by which WNT signaling function is peterbed in SCC tumours, are potentially diverse. Epigenetic inactivation of WNT signaling antagonists such as the SFRP genes is not restricted to cSCC, but rather is detected in a variety of other types of SCC tumours, including oral (Paluszczak, et al 2015;Pannone, et al 2010;Sogabe, et al 2008), oesphageal (Kishino, et al 2016;Liu, et al 2011;Meng, et al 2011;Saito, et al 2014;Yang, et al 2012), cervical (Delmas, et al 2011;Siegel, et al 2015) and head & neck (HN) SCCs (Marsit, et al 2006), and thus could represent a universal mechanism of WNT activation in SCC tumours.…”
Section: Wnt Signaling In Csccmentioning
confidence: 99%